KIRKHS thesis and dissertation abstracts (2003-2007) - Abushouk, Ahmed Ibrahim (IIUM Press, 2009)
This volume entitled KlRKHS Thesis and Dissertation Abstracts (2003-2007) acquaints researchers, students and other related practitioners who are interested in novel research undertaken by postgraduate students in a variety oftopics. The volume would assist them to chart new avenues in the light of informatfon supplied, and initiate meaningful dialogues in the areas of Islamic Revealed Knowledge and the Human Sciences. It also shows the flexibility and diversity in research by the Kulliyyah, which entails richness in the corpus of knowledge. The volume provides statistical information on the growth of student research at the postgraduate level in the Kulliyyah of Islamic Revealed Knowledge and Human Sciences, and the number of academic staffwho have contributed to the supervision ofMAand Ph.D. dissertations and theses in the last five academic years. (2003-2007). The set of figures provided i~ the introduction of this volume is based on the analysis of the total abstracts provided, illustrating the growth ofMA and Ph.D. students in the last five academic years (2003-2007), their distribution according to the degrees obtained and the affiliated departments, the percentage of international and local students as well as that of full-time and part-time students. Both the statistical survey and figures provide necessary information which would be helpful for the strategif plFing' for the forthcoming years in terms of student admission, improvement in teaching and learning facilities, and recruitment of academic staff in certain areas of specialization.